Desenvolvimento e avaliação de eletrodos de difusão gasosa (EDG) para geração de H2O2 in situ e sua aplicação na degradação do corante reativo azul 19 - Rocha, Robson S.; Reis, Rafael M.; Beati, André A. G. F.; Lanza, Marcos R. V.; Sotomayor, Maria Del Pilar Taboada [UNESP]; Bertazzoli, Rodnei (Sociedade Brasileira de Química, 2012)
This work reports the development of GDE for electrogeneration of H2O2 and their application in the degradation process of Reactive Blue 19 dye. GDE produced by carbon black with 20% polytetrafluoroethylene generated up to 500 mg L-1 of H2O2 through the electrolysis of acidic medium at -0.8 V vs Ag/AgCl. Reactive Blue 19 dye was degraded most efficiently with H2O2 electrogenerated in the presence of Fe(II) ions, leading to removal of 95% of the original color and 39% of TOC at -0.8 V vs Ag/AgCl.
Development and evaluation of gas diffusion electrodes (GDE) for generation of H2O2 in situ and their application in the degradation of reactive blue 19 dye
Keywords: gas diffusion electrode; hydrogen peroxide; Reactive Blue 19 dye